Pelatihan Adversity Intelligence Untuk Meningkatkan Kebermaknaan Hidup Remaja Panti Asuhan - Lisfarika Napitupulu; Fuad Nashori; Irwan Nuryana Kurniawan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2007)
This research try to investigate the influence of Adversity Intelligence training to life meaning among teenager in orphanage. Hypotheses proposed that possible difference of life meaning could exist before and after Adversity Intelligence training among teenager in the orphanage.Subjects participated in this research are 6 (six) teenager of Panti Asuhan Muhammadiyah Putra in Yogyakarta and 14-19 years old. Experimental design employed was Pretest-Post Test Design. Data analyzed through paired sample t-test.Research found that life meaning differences exist in subjects before and after training with t: -2.216 p: 0,039. It means that Adversity Intelligence training could increase life meaning among teenager in the orphanage. Key words    :    life meaning, Adversity Intelligence training